Halogen-free flame-retardant antistatic nylon and preparation method and application thereof
By using the coordinated addition of modified carbon nanotubes and halogen-free flame retardant in PA6 materials, the problem of insufficient electrostatic and flame retardant performance during friction is solved, and the efficient flame retardant and antistatic properties of the material are achieved, while improving the mechanical properties.
Patent Information
- Application Number
- CN202510284035.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyamide 6 (PA6) materials are prone to static electricity during friction, causing sparks and fires, and their flame retardant properties are insufficient, making it difficult to improve antistatic and flame retardant properties while maintaining mechanical properties.
By grafting spirocyclic pentaerythritol dichlorodichlorobisphosphate (SPDPC) on the modified carbon nanotubes, a bifunctional organosilane compound is formed, and a microencapsulated halogen-free flame retardant and a composite of modified carbon nanotubes and carbon fibers are added to the PA6 matrix to improve the flame retardant and antistatic properties of the material.
It significantly improves the flame retardant and antistatic properties of PA6 materials, while enhancing its mechanical properties, and can form a high-strength carbon layer during the combustion process, effectively isolate heat and air, and prevent the overflow of combustible gases and smoke.
Smart Images

Figure CN119775768A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon synthesis, in particular to a halogen-free flame-retardant antistatic nylon and a preparation method and application thereof. Background Art
[0002] Nowadays, polyamide 6 (PA6) products have good dimensional stability and extremely high surface hardness, tensile strength, bending strength and wear resistance. The strength of modified PA6 has exceeded that of general light metals, such as zinc and magnesium, and is close to that of aluminum. Therefore, polyamide 6 (PA6) has broad application prospects due to its excellent mechanical properties and high temperature resistance. Furthermore, modified PA6 is widely used to replace various non-ferrous metals to manufacture various parts in the machinery industry, such as gears, transmission parts, etc., and even for large load-bearing parts.
[0003] However, due to the insulation of PA6-based materials, the charges generated during friction cannot be transferred in time, and the accumulated charges on the surface will break through the air insulation, generate sparks, and ignite itself or surrounding combustibles to form a fire source. At the same time, because it exists in the form of covalent bonds with weaker bond energy, when it is burned by flames to obtain energy, these covalent bonds will break and generate free radicals, which will trigger a chain combustion reaction and the polymer will continue to burn, thus causing a fire. Therefore, it is very important to improve the flame retardant and antistatic properties of PA6.
[0004] At present, the main method is to add flame retardant and antistatic fillers during the synthesis of polyamide. However, there are few studies on improving the flame retardancy and antistatic properties of PA6 at the same time. Some commonly used flame retardants are added in large amounts, and excessive addition will lead to reduced mechanical properties of PA6 materials. Therefore, glass fiber is currently used to improve the strength of PA6, and flame retardant materials and conductive fillers are added to improve its flame retardancy and antistatic effects. Based on this, this application provides a better solution. Summary of the invention
[0005] The present application provides a halogen-free flame-retardant antistatic nylon and a preparation method and application thereof, which are used to improve the flame retardant and antistatic effects of PA6 and further increase the mechanical properties of PA6.
[0006] The present application provides a halogen-free flame retardant antistatic nylon, wherein the raw materials of the nylon mainly include a PA6 matrix, a POE graft, a nylon black masterbatch and a modified additive; the modified additive includes a flame retardant-antistatic synergistic additive, a lubricant, an antioxidant and a dispersant; the flame retardant-antistatic synergistic additive includes a microencapsulated halogen-free flame retardant and a composite of modified carbon nanotubes and carbon fibers; spiropentaerythritol dichlorophosphate (SPDPC) is grafted onto the modified carbon nanotubes through an organic silicon coupling agent to form a bifunctional organic silane compound; the specific structure of the spiropentaerythritol dichlorophosphate (SPDPC) is as follows: .
[0007] By adopting the above technical scheme, the present application grafts spiropentaerythritol dichlorophosphate (SPDPC) on the modified carbon nanotubes through an organic silicon coupling agent to form a bifunctional organic silane compound; currently, carbon nanotubes are used as conductive fillers, and the present application grafts a halogen-free flame-retardant rigid structure on the carbon nanotubes to improve its flame retardant effect. When the PA6 matrix is burned by flames, it can not only absorb a part of the free radicals, but also promote the formation of the carbon layer and improve the quality of the carbon layer. At the same time, the modified carbon nanotubes in the PA6 matrix act as a skeleton to improve the support of the carbon layer; in addition, the grafted spiropentaerythritol dichlorophosphate can improve the strength of the carbon layer, and the grafted silicon and phosphorus elements can also improve the strength of the carbon layer generated during combustion. This high-strength skeleton-supported carbon layer can effectively isolate the external heat and air during the combustion process, block the internal combustible gas and smoke from overflowing, and make the material incompletely burned, thereby improving the flame retardant properties of the material.
[0008] Preferably, the organosilicon coupling agent includes one or more of 3-aminopropyltrimethoxysilane, aminopropyltriethoxysilane, and ureapropyltriethoxysilane, and the organosilicon coupling agent forms a bifunctional organosilane compound with spiropentaerythritol dichlorophosphate (SPDPC) and is fixed on the modified carbon nanotubes.
[0009] By adopting the above technical scheme, the amino groups on the silicone coupling agent are fixed on both sides of spiropentaerythritol dichlorophosphate (SPDPC), so that the grafted silicon and phosphorus elements can also improve the strength of the carbon layer generated during combustion; in addition, with the addition of flame retardant materials, the mechanical properties of the PA6 material are improved due to the spatial support of the conductive material of the carbon nanotubes and the influence of the silane structure on the spatial structure of the spiropentaerythritol dichlorophosphate.
[0010] Preferably, the raw materials of the spiropentaerythritol dichlorophosphate (SPDPC) mainly include phosphorus oxychloride and pentaerythritol.
[0011] Preferably, the halogen-free flame retardant includes one or more of melamine cyanurate, melamine polyphosphate, ammonium polyphosphate, and diethyl aluminum phosphinate.
[0012] Preferably, the composite of the modified carbon nanotubes and carbon fibers further comprises poly-o-anisidine; the weight ratio of the modified carbon nanotubes, the carbon fibers and the poly-o-anisidine is (4-8): (8-15): (1-4).
[0013] By adopting the above technical solution, due to the extremely large aspect ratio of carbon nanotubes, there is a π-π interaction between carbon nanotubes and polymer matrix. In order to break the van der Waals force between carbon nanotubes on the modified carbon nanotubes, the carbon nanotubes are agglomerated in the polymer matrix. The present application grafts poly-o-anisidine on the vacancies on the surface of the modified carbon nanotubes, so that the van der Waals force is replaced by hydrogen bonds between the PA6 matrix and the modified carbon nanotubes, thereby promoting the uniform dispersion of the conductive filler modified carbon nanotubes in the polymer matrix, improving the compatibility of the modified carbon nanotubes and the PA6 matrix, and thus improving the performance of the composite material.
[0014] Preferably, in the flame retardant-antistatic synergistic additive, the weight ratio of the halogen-free flame retardant to the composite of the modified carbon nanotubes and carbon fibers is (2-5): (1-2).
[0015] On the other hand, the present application discloses a method for preparing halogen-free flame-retardant and antistatic nylon, comprising the following steps: S1, preparation of modified carbon nanotubes: dissolving spirocyclic pentaerythritol dichlorophosphate (SPDPC) and triethylamine in an acetonitrile solution in a certain proportion to obtain a mixed solution A; then dissolving a certain amount of an organosilicon coupling agent in another acetonitrile solution to obtain a mixed solution B, then dripping the mixed solution B into the mixed solution A for a certain period of time, stirring for a certain period of time under argon protection and certain constant temperature conditions, and filtering impurities such as triethylamine hydrochloride, filtering the filtered product under reduced pressure by rotary evaporation to obtain a yellow oily liquid, and dissolving it in a mixed solution of deionized water and ethanol, and then adding a certain amount of carbon nanotubes, stirring for a certain period of time at a certain temperature, washing with deionized water for multiple times to remove excess reagents, drying in a drying oven for a certain period of time, and finally grinding to obtain a black powder, i.e., modified carbon nanotubes; S2, flame-retardant-antistatic synergistic additives Preparation: adding a certain amount of the poly-o-anisidine to the meta-cresol solution, heating it to a certain temperature, and stirring until it is dissolved; adding the modified carbon nanotubes and the carbon fibers in proportion, placing them in an ultrasonic instrument, ultrasonically treating them for a certain time, and finally dispersing them at a certain speed with a high shear homogenizer for a certain time, and repeating the process for many times to obtain a composite solution of the modified carbon nanotubes and carbon fibers; then adding a certain proportion of a halogen-free flame retardant, stirring and dissolving them at a certain temperature, and finally placing them in a drying oven for drying for a certain time to obtain a flame retardant-antistatic synergistic additive; S3, synthesis of halogen-free flame retardant and antistatic nylon: adding PA6 matrix, POE grafted material, and nylon black masterbatch to a high-speed mixer for premixing, and then adding the flame retardant-antistatic synergistic additive, the lubricant, the antioxidant and the dispersant in proportion, and putting them into a high-speed mixer for premixing, premixing for a certain time, and then adding the premixed materials to the silo of the twin-screw extruder.
[0016] Preferably, the halogen-free flame retardant antistatic nylon or the halogen-free flame retardant antistatic nylon prepared by the preparation method of the halogen-free flame retardant antistatic nylon is used to manufacture various parts in the machinery industry, such as gear parts and transmission parts; and the halogen-free flame retardant antistatic nylon is used in the fields of automobiles, subways, ships and robots.
[0017] One or more technical solutions provided in this application have at least the following technical effects or advantages: 1. In the present application, spiropentaerythritol dichlorophosphate (SPDPC) is grafted onto modified carbon nanotubes by an organic silicon coupling agent to form a bifunctional organic silane compound, so that PA6 can not only absorb a part of free radicals during combustion, but also promote the formation of a carbon layer and improve the quality of the carbon layer. The modified carbon nanotubes in the PA6 matrix serve as a skeleton to improve the support of the carbon layer.
[0018] 2. The present application grafts spirocyclic pentaerythritol dichlorobisphosphate onto carbon nanotubes to improve the strength of the carbon layer, wherein the grafted silicon and phosphorus elements can also improve the strength of the carbon layer generated during combustion. This high-strength carbon layer with a skeleton support can effectively isolate external heat and air during the combustion process, block the internal combustible gas and smoke from overflowing, and make the material burn incompletely, thereby improving the flame retardant properties of the material.
[0019] 3. The amino hydrocarbon-based organosilicon coupling agent used in this application is grafted on spiropentaerythritol dichlorophosphate (SPDPC), and the amino functional groups therein can be fixed on both sides of spiropentaerythritol dichlorophosphate (SPDPC), thereby allowing the carbon nanotubes to have the spatial support of their conductive materials and the spatial structural support of the silane structure in the spiropentaerythritol dichlorophosphate, which is beneficial to improving the mechanical properties of the PA6 material.
[0020] 4. The present application grafts poly-o-anisidine onto the surface vacancies of the modified carbon nanotubes, so that hydrogen bonds are used between the PA6 matrix and the modified carbon nanotubes to replace the van der Waals forces, thereby promoting the uniform dispersion of the conductive filler modified carbon nanotubes in the polymer matrix, improving the compatibility of the modified carbon nanotubes and the PA6 matrix, and thus improving the performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 The synthetic structural expression of spiropentaerythritol dichlorophosphate (SPDPC) in the examples of this application; Figure 2 is a structural expression of the synthesis of 3-aminopropyltrimethoxysilane and spiropentaerythritol dichlorophosphate (SPDPC) in the embodiment of the present application; Figure 3 The structural expression of the synthesis of aminopropyltriethoxysilane and spiropentaerythritol dichlorophosphate (SPDPC) in the embodiment of the present application; Figure 4 The structural expression of the synthesis of ureapropyltriethoxysilane and spiropentaerythritol dichlorophosphate (SPDPC) in the embodiment of the present application; Figure 5 Schematic diagram of the structure of spirocyclopentaerythritol dichlorophosphate (SPDPC) grafted onto carbon nanotubes in the embodiments of the present application. DETAILED DESCRIPTION
[0023] The present application provides a halogen-free flame-retardant antistatic nylon and a preparation method and application thereof, which are used to improve the flame retardant and antistatic effects of PA6 and further increase the mechanical properties of PA6.
[0024] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product, or server that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or modules that are not clearly listed or inherent to these processes, methods, products, or devices.
[0026] raw material PA6 matrix: The PA6 matrix used in the embodiments of the present application is a masterbatch from a domestic nylon factory (model LC01 / 247).
[0027] POE grafts: The POE grafts used in the examples of the present application were grafted with POE maleic acid rods from a foreign chemical plant (model POEN216); Nylon black masterbatch: the nylon black masterbatch currently available in China used in the embodiments of the present application; 3-Aminopropyltrimethoxysilane: CAS No. 13822-56-5 Molecular weight 179.290: Aminopropyltriethoxysilane: CAS No. 919-30-2 Molecular weight 221.369: Ureapropyltriethoxysilane: CAS No. 23779-32-0 Molecular weight 264.394: Phosphorus oxychloride: CAS No. 10025-87-3, molecular weight 153.332, purity 99.5%; Pentaerythritol: CAS No. 115-77-5, molecular weight 136.146, purity 99.5%; Melamine cyanurate: CAS No. 37640-57-6, molecular weight 255.194, purity 99.5%; Melamine polyphosphate: CAS No. 15541-60-3, molecular weight 304.095, purity 99.5%; Ammonium polyphosphate: CAS No. 68333-79-9, molecular weight 149.087, purity 99.0%; Aluminum diethylphosphinate: CAS No. 225789-38-8, molecular weight 393.290, purity 99.0%.
[0028] Raw material example Preparation of spiropentaerythritol dichlorophosphate (SPDPC): Phosphorus oxychloride and pentaerythritol were added to the reactor together. The temperature was then raised to 120°C, argon was introduced for protection, sodium hydroxide solution was used to absorb the released hydrogen chloride gas, and the reaction solution was stirred at a constant temperature until no HCI was released. When the temperature of the reaction system dropped to room temperature, the filtered product was washed with chloroform and ether, and a white powder product, spiropentaerythritol dichloro bisphosphate, was obtained after reduced pressure distillation by rotary evaporation.
[0029] Preparation of poly-o-anisidine: The present invention adopts o-anisidine (OMA) as a monomer, ammonium persulfate (APS) as an oxidant, p-toluenesulfonic acid (p-TSA) as a dopant, and adopts a chemical oxidation method to synthesize a conductive polymer poly-o-anisidine. Example
[0030] Example 1
[0031] S1. Preparation of modified carbon nanotubes: 300 g of spirocyclopentaerythritol dichlorobisphosphate and 200 g of triethylamine were dissolved in 1.5 L of acetonitrile solution in proportion to obtain a mixed solution A; 1.2 kg of 3-aminopropyltrimethoxysilane was dissolved in another 0.5 L of acetonitrile solution to obtain a mixed solution B, and then the mixed solution B was dripped into the mixed solution A within 5 hours, stirred for 24 hours under argon protection and a constant temperature of 45°C, and impurities such as triethylamine hydrochloride were filtered, and the filtered product was filtered under reduced pressure by rotary evaporation to obtain a yellow oily liquid, which was dissolved in a mixed solution of deionized water and ethanol (the weight ratio of deionized water to ethanol was 1:1), and then 100 g of carbon nanotubes were added, and after stirring at 80°C for 12 hours, the excess reagents were removed by washing with deionized water for several times, and the mixture was dried in a drying oven at 80°C for 12 hours, and finally ground to obtain a black powder, i.e., the modified carbon nanotubes; S2. Preparation of flame retardant-antistatic synergistic additive: add 100g of the poly-o-anisidine to 1.5L of m-cresol solution, heat to 60°C, and stir until dissolved; add 400g of modified carbon nanotubes and 800g of carbon fibers, place in an ultrasonic instrument, and ultrasonicate for 1h, and finally disperse with a high shear homogenizer at 8000r / min for 20min, and repeat three times to obtain a composite solution of modified carbon nanotubes and carbon fibers; then weigh 100g of the composite solution, add 200g of microencapsulated melamine cyanurate, stir to dissolve at a certain temperature, and finally place in a drying oven at 80°C for 24h to obtain a flame retardant-antistatic synergistic additive; S3, Synthesis of halogen-free flame retardant and antistatic nylon: 12.0kg of PA6 matrix, 0.5kg of POE graft, and 0.8kg of nylon black masterbatch were added to the high-speed mixer for premixing for 10 minutes, followed by adding 2.0kg of flame retardant-antistatic synergistic additives, 0.5kg of lubricant (P130), 0.5kg of antioxidant (1010), 0.5kg of antioxidant (168) and 0.2kg of dispersant glass fiber TAF, and put into the high-speed mixer for premixing, premixing for 0.5h, and then the premixed materials were added to the twin-screw extruder silo. The screw speed was 330r / min, the main material loss-in-weight scale was 70kg / hour; the side feed 1 loss-in-weight scale (carbon fiber) was 15kg / hour; the side feed 2 loss-in-weight scale (glass fiber) was 15kg / hour. The current is: 35A; the extrusion temperature is: zone 1 180℃, zone 2 230℃, zone 3 230℃, zone 4 230℃, zone 5 220℃, zone 6 190℃, zone 7 190℃, zone 8 190℃, zone 9 200℃, zone 10 200℃, die head temperature 240℃; vacuum pressure: 0.08Mpa-0.09Mpa; pelletizer speed: 200r / min.
[0032] The raw material example discloses the preparation of spirocyclopentaerythritol dichlorophosphate (SPDPC). Figure 1 , discloses a synthetic structural expression of spiropentaerythritol dichlorophosphate (SPDPC), wherein a three-dimensional structure of a flame retardant with chlorophosphate structures on both sides is obtained by constructing the structure of spiropentaerythritol dichlorophosphate.
[0033] The present invention grafts spirocyclic pentaerythritol dichlorophosphate onto carbon nanotubes by using 3-aminopropyl trimethoxysilane, wherein the reaction structure of 3-aminopropyl trimethoxysilane and spirocyclic pentaerythritol dichlorophosphate is as follows: Figure 2As shown, spiropentaerythritol dichlorophosphate (SPDPC) is grafted by an amino hydrocarbon-based organosilicon coupling agent, in which the amine functional groups can be fixed on both sides of the spiropentaerythritol dichlorophosphate (SPDPC) to obtain a flame-retardant spatial structure with Si-R as the skeleton. The silane structure is used to support the spatial structure of the spiropentaerythritol dichlorophosphate to improve the mechanical properties of the PA6 material.
[0034] It should be noted that the chlorine elements in the dichlorophosphate on both sides of the spiropentaerythritol dichlorophosphate (SPDPC) in the present application are fully reacted and replaced by the silane coupling agent, so the flame-retardant and antistatic nylon used in actual production and application is halogen-free nylon.
[0035] Further, see Figure 5 , Si-R is grafted onto carbon nanotubes, so that a flame-retardant spatial structure with Si-R as the skeleton is constructed on the surface of the carbon nanotubes to improve the mechanical properties of the PA6 matrix.
[0036] In addition, Figure 5 As shown in the figure, due to the large aspect ratio of carbon nanotubes, there is a π-π interaction between carbon nanotubes and the polymer PA6 matrix. In order to break the van der Waals force between carbon nanotubes, the carbon nanotubes are agglomerated in the polymer matrix.
[0037] The present application has ungrafted vacancies on the surface of the modified carbon nanotubes, and grafts poly-o-anisidine during the preparation of the flame retardant-antistatic synergistic additive, so that hydrogen bonds are used between the PA6 matrix and a partial region of the modified carbon nanotubes to replace the van der Waals force, thereby promoting the uniform dispersion of the conductive filler modified carbon nanotubes in the polymer matrix, improving the compatibility of the modified carbon nanotubes with the PA6 matrix, and thereby improving the performance of the composite material.
[0038] Example 2
[0039] The difference between Example 2 and Example 1 is that, in the preparation process of modified carbon nanotubes, aminopropyl triethoxysilane is used to graft spirocyclic pentaerythritol dichlorophosphate onto carbon nanotubes, wherein the specific synthetic structural formula is as follows: Figure 3 shown.
[0040] Example 3
[0041] The difference between Example 3 and Example 1 is that, in the preparation process of modified carbon nanotubes, ureapropyl triethoxysilane is used to graft spirocyclic pentaerythritol dichlorophosphate onto carbon nanotubes, wherein the specific synthetic structural formula is as follows: Figure 4 shown. Comparative Example
[0042] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that, in the preparation process of modified carbon nanotubes, an organic silicon coupling agent is used to modify the surface of the carbon nanotubes, and spiropentaerythritol dichlorophosphate (SPDPC) is not grafted onto the carbon nanotubes.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that, in the preparation process of the flame retardant-antistatic synergistic additive, poly-o-anisidine is not mixed with the modified carbon nanotubes and carbon fibers.
[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that, in the preparation process of modified carbon nanotubes, spiropentaerythritol dichlorophosphate (SPDPC) is not grafted onto carbon nanotubes; and in the preparation process of flame retardant-antistatic synergistic additives, poly-o-anisidine is not mixed with modified carbon nanotubes and carbon fibers.
[0045] Performance testing experiment The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the results are shown in Table 1. The test standard for tensile properties is GB / T 1040.5-2008; the test standard for bending properties is GB / T 1449-2005; the test standard for flame retardancy is GB / T 2408-2021; and the test standard for antistatic properties is GB / T 39587-2020.
[0046] Table 1 Performance test of halogen-free flame retardant antistatic nylon prepared in Examples 1-3 and Comparative Examples 1-3
[0047] According to the analysis between Example 1 and Comparative Example 1, it can be obtained that in the preparation process of modified carbon nanotubes, an organic silicon coupling agent is used to modify the surface of the carbon nanotubes, and spiropentaerythritol dichlorophosphate (SPDPC) is grafted onto the carbon nanotubes. It can increase certain mechanical properties, because the amino functional groups are fixed on both sides of the spiropentaerythritol dichlorophosphate, and then a flame-retardant space structure with Si-R as the skeleton has a spatial support effect on the PA6 matrix. At the same time, because the silicon element and phosphorus element synthesized by the spiropentaerythritol dichlorophosphate and the organic silicon coupling agent can improve the strength of the carbon layer generated during combustion, this high-strength carbon layer with skeleton support can effectively isolate the external heat and air during the combustion process, block the internal combustible gas and smoke from overflowing, make the material incompletely burned, and thus improve the flame retardant properties of the material.
[0048] Combined with the analysis of Comparative Examples 2 and 3, it can be concluded that grafting poly-o-anisidine on the vacancies on the surface of the modified carbon nanotubes can replace the van der Waals force between the PA6 matrix and the modified carbon nanotubes through hydrogen bonds, promote the uniform dispersion of the conductive filler modified carbon nanotubes in the polymer matrix, and improve the compatibility of the modified carbon nanotubes with the PA6 matrix. At the same time, poly-o-anisidine is a good conductive filler that can improve the conductive effect of PA6 and reduce the probability of static electricity.
[0049] Furthermore, from the analysis of Examples 1-3, it can be concluded that when spirocyclic pentaerythritol dichlorobisphosphate is grafted onto carbon nanotubes through 3-aminopropyltrimethoxysilane during the preparation of modified carbon nanotubes, it can have better spatial structural resistance, and its mechanical properties are better than those of Examples 2 and 3.
[0050] Embodiment 4-6 The difference between Example 4 and Example 1 is that, during the preparation of the flame retardant-antistatic synergistic additive, microencapsulated melamine polyphosphate is added to the composite solution of modified carbon nanotubes and carbon fibers.
[0051] The difference between Example 5 and Example 1 is that, during the preparation of the flame retardant-antistatic synergistic additive, microencapsulated ammonium polyphosphate is added to the composite solution of modified carbon nanotubes and carbon fibers.
[0052] The difference between Example 6 and Example 1 is that, during the preparation of the flame retardant-antistatic synergistic additive, microencapsulated diethyl aluminum phosphinate is added to the composite solution of modified carbon nanotubes and carbon fibers.
[0053] Performance testing experiment The composite materials prepared in Examples 1, 4-6 were subjected to performance tests, and the results are shown in Table 2. The test standard for tensile properties is GB / T 1040.5-2008; the test standard for bending properties is GB / T 1449-2005; the test standard for flame retardancy is GB / T 2408-2021; and the test standard for antistatic properties is GB / T 39587-2020.
[0054] Table 2 Performance test of halogen-free flame retardant antistatic nylon prepared in Examples 1, 4-6
[0055] According to the analysis between Example 1 and Examples 4-6, the flame retardant grades in the flame retardant tests all reached the V0 level, but the difference in flame retardant materials will change the spatial structure of the modified carbon nanotubes and thus change the mechanical properties and antistatic effect of the flame retardant and antistatic PA6 during the preparation of the flame retardant-antistatic synergistic additive. According to the analysis of experimental data, Example 4 is the best example.
[0056] In addition, during the experiment, the types of flame retardant materials were changed in Examples 4-6 of the present application, and the carbon layers were analyzed to find that the spatial structure of the modified carbon nanotubes was conducive to the fixation of the flame retardant materials, and the silicon element could increase the strength of the carbon layer when the material burned, so the carbon layer produced by its combustion was relatively continuous and relatively strong, blocking the release of part of the smoke. Although the flame retardant effects of Examples 1 and Examples 4-6 all reached the V0 level, it was found that Examples 1 and Example 4 extinguished themselves faster after burning than Examples 5 and 6.
[0057] The nylon material in this application has high strength, good toughness, good fluidity, halogen-free flame retardant, antistatic, and good wear resistance, so it is used to manufacture various parts in the machinery industry, such as gear parts and transmission parts; and the halogen-free flame retardant antistatic nylon is used in the fields of automobiles, subways, ships, and robots. Specifically, due to its unique antistatic and flame retardant effects, it is suitable for the drag chain system of robot arms, thereby effectively reducing the electric shock caused by friction static electricity accumulation, and has both flame retardant effects and long-term practicality, effectively solving static electricity problems, parts wear problems, flame retardant problems, etc. in practical applications.
[0058] It should be noted that the above-mentioned sequence of the embodiments of the present application is only for description and does not represent the advantages and disadvantages of the embodiments. And the above-mentioned specific embodiments of this specification are described. Other embodiments are within the scope of the attached claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.
[0059] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.
[0060] This specification and drawings are merely exemplary illustrations of the present application and are deemed to cover any and all modifications, variations, combinations or equivalents within the scope of the present application. Obviously, a person skilled in the art may make various modifications and variations to the present application without departing from the scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the present application and its equivalents, the present application intends to include these modifications and variations.
Claims
1. A halogen-free flame-retardant antistatic nylon, characterized in that: The raw materials of the nylon mainly include PA6 matrix, POE graft, nylon black masterbatch and modified additives; the modified additives include flame retardant-antistatic synergistic additives, lubricants, antioxidants and dispersants; The flame retardant-antistatic synergistic additive comprises a microencapsulated halogen-free flame retardant and a compound of modified carbon nanotubes and carbon fibers; The modified carbon nanotubes are grafted with spiropentaerythritol dichlorophosphate (SPDPC) through an organic silicon coupling agent to form a bifunctional organic silane compound; the specific structure of the spiropentaerythritol dichlorophosphate (SPDPC) is as follows: 。 2. The halogen-free flame-retardant antistatic nylon according to claim 1, characterized in that: The organic silicon coupling agent includes one or more of 3-aminopropyltrimethoxysilane, aminopropyltriethoxysilane and ureapropyltriethoxysilane. The organic silicon coupling agent forms a bifunctional organic silane compound with spirocyclopentaerythritol dichlorophosphate (SPDPC) and is fixed on the modified carbon nanotube.
3. The halogen-free flame-retardant antistatic nylon according to claim 1, characterized in that: The raw materials of the spiropentaerythritol dichlorophosphate (SPDPC) mainly include phosphorus oxychloride and pentaerythritol.
4. The halogen-free flame-retardant antistatic nylon according to claim 1, characterized in that: The halogen-free flame retardant includes one or more of melamine cyanurate, melamine polyphosphate, ammonium polyphosphate, and diethyl aluminum phosphinate.
5. The halogen-free flame-retardant antistatic nylon according to claim 4, characterized in that: The modified carbon nanotube and carbon fiber compound further includes poly-o-anisidine; The weight ratio of the modified carbon nanotube, the carbon fiber and the poly-o-anisidine is (4-8): (8-15): (1-4).
6. The halogen-free flame-retardant antistatic nylon according to claim 5, characterized in that: In the flame retardant-antistatic synergistic additive, the weight ratio of the halogen-free flame retardant to the composite of the modified carbon nanotubes and carbon fibers is (2-5): (1-2).
7. A method for preparing the halogen-free flame-retardant antistatic nylon according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparation of modified carbon nanotubes: spirocyclopentaerythritol dichlorophosphate (SPDPC) and triethylamine are dissolved in an acetonitrile solution in a certain proportion to obtain a mixed solution A; a certain amount of an organosilicon coupling agent is dissolved in another acetonitrile solution to obtain a mixed solution B, and then the mixed solution B is dripped into the mixed solution A for a certain period of time, stirred for a certain period of time under argon protection and a certain constant temperature condition, and impurities such as triethylamine hydrochloride are filtered, and the filtered product is filtered under reduced pressure by rotary evaporation to obtain a yellow oily liquid, and the oily liquid is dissolved in a mixed solution of deionized water and ethanol, and then a certain amount of carbon nanotubes is added, and after stirring for a certain period of time at a certain temperature, the excess reagent is removed by washing with deionized water for multiple times, and the mixture is dried in a drying oven for a certain period of time, and finally ground to obtain a black powder, i.e., the modified carbon nanotubes; S2. Preparation of flame retardant-antistatic synergistic additive: adding a certain amount of the poly-o-anisidine to the m-cresol solution, heating it to a certain temperature, and stirring it until it is dissolved; adding the modified carbon nanotubes and the carbon fibers in proportion, placing them in an ultrasonic instrument, ultrasonically treating them for a certain time, and finally dispersing them at a certain speed with a high shear homogenizer for a certain time, and repeating the process for multiple times to obtain a composite solution of the modified carbon nanotubes and the carbon fibers; then adding a certain proportion of a halogen-free flame retardant, stirring and dissolving at a certain temperature, and finally placing them in a drying oven for drying for a certain time to obtain a flame retardant-antistatic synergistic additive; S3. Synthesis of halogen-free flame-retardant and antistatic nylon: Add PA6 matrix, POE graft and nylon black masterbatch into a high-speed mixer for premixing, then add the flame-retardant-antistatic synergistic additive, the lubricant, the antioxidant and the dispersant in proportion, and put into the high-speed mixer for premixing. Premix for a certain period of time, and then add the premixed materials into the silo of the twin-screw extruder.
8. The halogen-free flame retardant antistatic nylon according to any one of claims 1 to 6 or the halogen-free flame retardant antistatic nylon prepared by the preparation method of the halogen-free flame retardant antistatic nylon according to claim 7, characterized in that: It is used to manufacture various parts in the machinery industry, such as gear parts and transmission parts; and the halogen-free flame-retardant antistatic nylon is used in the fields of automobiles, subways, ships and robots.
Citation Information
Patent Citations
Trace buckle
CA115775A
Bottle stopper
CA153332A
Novel flame retardant containing phosphorus and preparation method thereof
CN102504268A
Halogen-free flame-retardant toughened nylon as well as preparation method and application thereof
CN110615987A
Halogen-free flame-retardant long glass fiber reinforced nylon 12 material with high RTI value as well as preparation method and application of halogen-free flame-retardant long glass fiber reinforced nylon 12 material
CN112876841A
Cited By
Ultra-dispersed flame-retardant engineering plastic master batch and preparation method thereof
CN120272005A
Anti-static plastic particles for processing plastic products and preparation method of anti-static plastic particles
CN120775383A
Halogen-free compound flame retardant and application thereof in antistatic nylon 66 composite material
CN121136199A